Cardiac hypertrophy and sudden death in mice with a genetically clamped renin transgene - Caron, Kathleen M. I. (National Academy of Sciences, 2004)
Several mouse models have already proved valuable for investigating hypertrophic responses to cardiac stress. Here, we characterize one caused by a well defined single copy transgene, RenTgMK, that genetically clamps plasma renin and thence angiotensin II at high levels. All of the transgenic males develop concentric cardiac hypertrophy with fibrosis but without dilatation. Over half die suddenly aged 6-8 months. Telemetry showed disturbances in diurnal rhythms a few days before death and, later, electrocardiographic disturbances comparable to those in humans with congestive heart failure. Expression of seven hypertrophy-related genes in this and two categorically different models (lack of atrial natriuretic peptide receptor A; overexpression of calsequestrin) were compared. Statistical analyses show that ventricular expressions of the genes coding for atrial natriuretic peptide, β myosin heavy chain, medium chain acyl-CoA dehydrogenase, and adrenomedullin correlate equally well with the degree of hypertrophy, although their ranges of expression are, respectively, 50-, 30-, 10-, and 3-fold.